Distribution and utilization of bamboos in the midwestern and the far-western regions of Nepal - Das, AN; Thapa, HB (Banko Janakari, 2013)
The distribution and utilization of bamboo species in the mid-western and the far-western regions were recorded using various methods including Rapid Rural Appraisal (RRA) and Participatory Rural Appraisal (PRA) tools, field visits and specimen collection. Of the eleven genera of bamboo recorded from the regions, most of the species were found to be of indigenous types. In the mid-western region, 48 bamboo species were recorded: 18 identified at species level and 11 at genera level. However, 19 species could not be identified, although their local names were recorded. Similarly, in the far-western region, 31 species were recorded: 10 were identified at species as well as genera levels. In this region too, 11 species could not be identified, only local names were recorded. Greater diversity of bamboos exists in the hills than in the Terai belt of the regions studied. High Mountain districts such as Jumla, Dolpa, and Darchula contain considerably less quantity of large diameter sized bamboos (bans) than small sized diameter bamboos (nigalo). Although, in these regions, 18 uses of bamboo were noted, many species are mostly used for weaving. The development of bamboo resources in the regions can help reduce poverty, generate employment and sustain rural livelihoods. DOI: http://dx.doi.org/10.3126/banko.v21i1.9059 Banko Janakari, Vol. 21, No. 1 2011; 13-24